ON NEW EXOTIC ATTEMPTS TO QUESTION THE RELATIONSHIP BETWEEN CITEDNESS FIGURES AND THE USE / VALUE OF CITED SCIENTIFIC DOCUMENTS - LAZAREV, Vladimir S. (University Library at a New Stage of Social Communications Development. Conference Proceedings, 2021)
The objective of the present paper was to analyze a number of concepts related to the scientometric method "citation index". Some experts still interpret “negative citations” and “disproportionately large share of self-citations” as “shortcomings” of the “citation index” scientometric method. In the author’s opinion, the reason is an indelible belief in the “normative theory of citation”, which implies a conscious choice of citations, a conscientious selection of the best quality works for the reference-lists, and a “desire to return the intellectual debt” to the cited authors. But there are also new attempts to question the adequacy of the “citation index” method. For example, one of the publications of the year 2020 questions the causal relationship between the citations to the scientific documents and their use, and between their use and their value; the reason why this fundamental pattern is called into question is mainly based on the actions of some people who do not meet ethical standards and may be arbitrarily directed against its manifestation. The mentioned paper claims, in particular, that very common are the following phenomena: deliberate refusal to use the necessary scientific documents; refusal to cite the documents used (including plagiarism and restraint from citing for technical reasons); practice of evaluating little-known and inaccessible documentary sources as not valuable enough (value is confused with quality in this case); fake citing to unread works. The present article refutes the interpretation of these phenomena as indicating the absence of the considered causal relationship and tries to demonstrate that, on the contrary, some of them are involuntary confirmation of the adequacy of the “citation index” method.